The Influence Of Learning Media And Learning Models On Learning Outcomes Through Mathematics Literacy Ability - Arofah, Irvana; Ningsi , Besse Arnawisuda; Sessu, Andi (IJBLE Scientific Publications Community Inc., 2023)
Learning outcomes are a measure of the success of the learning process. There are many factors involved in measuring learning outcomes. Learning media, learning models, and students' mathematical literacy abilities are important factors or variables in the learning process to achieve the best learning outcomes. This study aims to look at the direct and indirect effects of these three variables on learning outcomes with mathematical literacy skills as a mediating variable. This research was conducted on 122 students of the Mathematics Study Program at Pamulang University. The research method used is Structural Equation Modeling with the Smart-PLS 3.0 analysis tool. The results of the convergent validity test showed that the loading factor value was > 0.7 and the AVE value > 0.5 indicated that all indicators were valid. The reliability test shows a composite reliability value and Cronbach's alpha > 0.7 is said to be reliable. Learning media has a positive effect that is not significant on mathematical literacy skills. The learning model has a significant positive effect on mathematical literacy skills. Mathematical literacy ability has a significant positive effect on learning outcomes. Learning media has a significant positive effect on learning outcomes. Learning models have a positive but not significant effect on learning outcomes. Learning media has a positive influence that is not significant on learning outcomes through mathematical literacy skills.